Rational design of MnO2@MnO2 hierarchical nanomaterials and their catalytic activities. Issue 47 (24th October 2016) - Zhang, Bentian; Cheng, Gao; Ye, Wenjin; Zheng, Xiaoying; Liu, Hengfa; Sun, Ming; Yu, Lin; Zheng, Yuying; Cheng, Xiaoling
Abstract : Lavender-like α-MnO2 @α-MnO2 and balsam pear-like α-MnO2 @γ-MnO2 were prepared and α-MnO2 @γ-MnO2 exhibited a better performance than that of α-MnO2 @α-MnO2 in dimethyl ether combustion. Abstract : Hierarchically structured materials have special properties and possess potential in applications in the catalytic and electrochemical fields. Herein, two kinds of hierarchical core–shell nanostructures, lavender-like α-MnO2 @α-MnO2 and balsam pear-like α-MnO2 @γ-MnO2, were prepared by a facile room-temperature method using α-MnO2 nanowires as a backbone under acidic and alkaline conditions, respectively. When being used as a catalyst for dimethyl ether combustion, α-MnO2 @γ-MnO2 exhibited a better performance than α-MnO2 @α-MnO2 ( T 10 = 171 vs. 196 °C; T 90 = 220 vs. 258 °C, SV = 30, 000 mL g −1 h −1 ). It is concluded that the larger surface area, higher reducibility/oxygen mobility, richer surface oxygen species, and the relatively smaller apparent activation energy are responsible for the superior performance of α-MnO2 @γ-MnO2 .